Numerical study for battery thermal management system improvement with air channel in electric vehicles - Tugan, Volkan; Yardimci, Ugurcan (Elsevier, 2023)
In order to ensure the safe and efficient operation of the battery system in electric vehicles, the heat generated in the batteries must be rapidly removed from the system. Therefore, a battery thermal management system is needed to ensure that the battery pack operates at appropriate temperatures. This study focuses on improving the battery thermal management system in electric vehicles. For this purpose, two different types of battery modules with new air channel design were created. The temperature distribution, maximum temperature difference and pressure drop in the battery modules were numerically investigated with computational fluid dynamics. In addition, the effect of three different air velocities (1 m/s, 2 m/s and 3 m/s) on the battery temperature was evaluated. The results showed that the maximum temperature and maximum temperature difference in the battery decreased with the increase of the air inlet velocity. It was observed that the maximum temperature difference obtained for design 2 and design 3 decreased in the range of 15.01-17.93 % and 7.25-12.22 %, respectively, compared to Design 1.
Keywords: Battery thermal management system; Electric vehicle; CFD; Battery cooling; Battery technologies